Aleutian Mink Disease Virus and Humans - Jørgen R. Jepsen; Francesco d’Amore; Ulrik Baandrup; Michael Roost Clausen; Elisabeth Gottschalck; Bent Aasted (Emerging Infectious Diseases, 2009)
Reports of a possible relationship between Aleutian mink disease parvovirus (AMDV) and human infection are rare. However, 2 mink farmers with vascular disease and microangiopathy similar to that in mink with Aleutian disease were found to have AMDV-specific antibodies and AMDV DNA. These findings raise the suspicion that AMDV may play a role in human disease.